Eficiencia de tratamiento fungicida en semillas de garbanzo frente a A. rabiei - Pastor, Silvina Estela; Pérez, A.; Bustamante, Macarena; Pugliese, Bruno Daniel; Crociara, Clara Sonia; Spring, E.; Valetti, Lucio (Asociación de Laboratorios Agropecuarios Privados ( ALAP), 2020)
Poster